KONSTRUKSI KEMAMPUAN MENULIS NARATIF SISWA SEKOLAH DASAR MELALUI PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN BERBASIS DEEP LEARNING STUDI FENOMENOLOGIS - Farida Nugrahani; Ande Darma; Arnindya Ayu Nur Kusuma Arum; Sri Maryati; Susanti Ekasari; Tsuroyyatul Humaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the construction of elementary school students' narrative writing skills through the use of Artificial Intelligence (AI) in deep learning-based instruction. This study used qualitative methods with a phenomenological design to understand students' learning experiences in depth. Data were collected through in-depth interviews, classroom observations, and analysis of student writing. The results indicate that AI assists students in generating ideas, structuring texts, and developing language expression, while the deep learning approach encourages active engagement and in-depth reflection. The construction of narrative writing skills occurs through an iterative process involving exploration, interpretation, and reconstruction of ideas. Students demonstrated increased creativity and coherence in their writing, despite challenges in digital literacy and critical thinking skills. This study concludes that the integration of AI in deep learning-based instruction significantly contributes to the development of students' narrative writing skills through deeper cognitive and reflective processes.